Characterization of Brazilian spring wheat germplasm and its potential for increasing wheat genetic diversity in Canada - Rosa, Silvia Barcellos; Humphreys, Gavin; Langille, Linda; Voldeng, Harvey; Henriquez, Maria Antonia; Burt, Andrew James; Randhawa, Harpinder Singh; Fetch, Tom; Hiebert, Colin W.; Blackwell, Barbara; Zegeye, Taye; Cummiskey, Allan; et al. (Frontiers in Genetics, 2023)
In the present era of climate instability, Canadian wheat production has been frequently affected by abiotic stresses and by dynamic populations of pathogens and pests that are more virulent and aggressive over time. Genetic diversity is fundamental to guarantee sustainable and improved wheat production. In the past, the genetics of Brazilian cultivars, such as Frontana, have been studied by Canadian researchers and consequently, Brazilian germplasm has been used to breed Canadian wheat cultivars. The objective of this study was to characterize a collection of Brazilian germplasm under Canadian growing conditions, including the reaction of the Brazilian germplasm to Canadian isolates/pathogens and to predict the presence of certain genes in an effort to increase genetic diversity, improve genetic gain and resilience of Canadian wheat. Over 100 Brazilian hard red spring wheat cultivars released from 1986 to 2016 were evaluated for their agronomic performance in eastern Canada. Some cultivars showed good adaptability, with several cultivars being superior or statistically equal to the highest yielding Canadian checks. Several Brazilian cultivars had excellent resistance to leaf rust, even though only a few of these tested positive for the presence of either Lr34 or Lr16, two of the most common resistance genes in Canadian wheat. Resistance for stem rust, stripe rust and powdery mildew was variable among the Brazilian cultivars. However, many Brazilian cultivars had high levels of resistance to Canadian and African - Ug99 strains of stem rust. Many Brazilian cultivars had good Fusarium head blight (FHB) resistance, which appears to be derived from Frontana. In contrast FHB resistance in Canadian wheat is largely based on the Chinese variety, Sumai-3. The Brazilian germplasm is a valuable source of semi-dwarf (Rht) genes, and 75% of the Brazilian collection possessed Rht-B1b. Many cultivars in the Brazilian collection were found to be genetically distinct from Canadian wheat, making them a valuable resource to increase the disease resistance and genetic variability in Canada and elsewhere.